Role and Influence of Children in Buying Children's Apparel - Sharma, Adya (Indian Journal of Marketing, 2009)
The role of children in the buying process has increased over the years. Though a lot of research has been done in the West in understanding children's purchase influence, the need is also felt in the Indian context. This paper attempts to understand the role and influence of children in buying apparel. The opinion of the parents was also taken. The results indicate the growing importance of children in terms of taking their own decisions and also the discrepancy in the views of the parents and children.